THE TWIN REVOLUTIONS: A SYSTEMATIC REVIEW OF HUMAN CAPITAL MANAGEMENT AT THE NEXUS OF DIGITAL TRANSFORMATION AND SUSTAINABILITY - Abdullah, Sawab; Fitra, Arif Zakaria; Agustini, Rooswanti Putri Adi; Tutuko, Bambang; Kustyadji, Gatot; Bajuber, Jihan Salsabilla (Proceedings of the International Conference of Islamic Economics and Business (ICONIES); Vol 11 No 1 (2025): The 11th International Conference of Islamic Economics and Business (ICONIES 2025), 2025)
Human Capital Management (HCM) is undergoing a fundamental transformation, driven by the concurrent and deeply interconnected forces of rapid digitalization and the escalating demand for corporate accountability on Environmental, Social, and Governance (ESG) imperatives. This systematic literature review maps, synthesizes, and critically analyzes the scholarly literature on HCM published between 2020 and 2025 to understand this paradigm shift. Adopting a qualitative systematic literature review (SLR) approach, guided by PRISMA protocols, this study analyzes peer-reviewed articles from the Scopus database. The results identify three core thematic pillars shaping contemporary HCM: (1) the algorithmic reshaping of the workforce through AI and automation, which enhances efficiency but introduces significant implementation and skill-gap challenges; (2) the critical ethical imperative to govern AI-driven HCM, focusing on mitigating algorithmic bias, ensuring data privacy, and maintaining transparency; and (3) the sustainability mandate, which integrates ESG principles into HCM through practices like Green HRM and a focus on employee well-being and diversity. The discussion synthesizes these themes, arguing that the future of HCM lies at the integrated nexus of technology and sustainability, where "algorithmic legitimacy" and an "HCM-ESG Flywheel" emerge as new sources of competitive advantage. The review identifies critical research gaps, including a lack of cross-national studies and robust metrics for sustainable HCM, and proposes a forward-looking research agenda. This paper contributes an integrated framework for understanding how organizations can navigate the twin revolutions to build a workforce that is not only productive and innovative but also equitable, ethical, and sustainable.